African Studies in the Czech Republic-from the early Czech-African contacts until the 21st century - Záhořík, Jan (AAeO - Afrikanistik-Aegyptologie-Online, 2006)
We cannot talk about African Studies in the Czech Republic without first mentioning the preceding tradition of mutual Czech-African relations. The Czech Republic has quite a unique position among other countries of Central or Eastern Europe for its long tradition of travelling to the African interior.